Realizacja polityki innowacyjnej państwa — podmioty i sposoby realizacji - Popowska, Bożena (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article discusses the participation of entities of the public administration apparatus in the realization of state innovation policy — using the example of the Polish Agency for Enterprise Development and entities operating in the private research sector with an innovative profile, such as research and development centres. The article presents the forms of realization of state innovation policy, emphasizing the co-occurrence of public-legal and private-legal solutions within the legal construction and operation of both entities.
Keywords: innovation policy; public policy; Polish Agency for Enterprise Development; research sector; state agencies